Media Sosial dan Keterlibatan Politik Generasi Z pada Pilkada Kabupaten Enrekang Tahun 2024 - Qalbuadi, Galih Qrisnanda; Muhammad, Muhammad; Saad, Muhammad (Universitas Muhammadiyah Sorong, 2025)
Social media has become a primary space for Generation Z to express political views and engage in public participation, yet understanding of how this unfolds in the context of the 2024 Enrekang regional election remains limited. This study aims to describe the forms of digital political participation among Generation Z and the factors that shape their engagement. Using a descriptive qualitative approach based on a literature review, this study analyzes scholarly works discussing digital political participation, youth behavior, and the use of social media within local political processes. The findings indicate that the digital activities of Generation Z are diverse, adaptable to both local and national issues, and influenced by social norms, technological competence, and access to digital media. Despite challenges such as limited digital understanding and the risk of inaccurate information, digital platforms remain a space actively used by young people to participate in local political dynamics. This study concludes that these patterns require further exploration through field research to better understand communication strategies that align with the characteristics of Generation Z.